(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
One of the Eastern scholars, Voiz Kashifi’s ideas on governance, leadership, justice, and social organization were appreciated in his time and were used in textbooks for teaching in the education system. In particular, his books such as "Akhloqi Muhsini" and "Futuvvatnomai Sultani" contain profound views on leadership, managing people, etiquette, and moral standards. Kashifi advocated building governance on the basis of human qualities, wisdom, and justice, and emphasized honesty, hard work, and service to the people as responsibilities for leaders. The article attempts to shed light on the socio-political views of Voiz Kashifi. A famous orator and a high moralist in his time, Kashifi’s socio-political views, which gave perfect advice and recommendations in his sermons, are also important for today’s governance and can serve as a practical program in training leadership personnel. The position and role of the leader, the norms of his policy are reflected in Koshifi’s views and are analyzed in the article in accordance with today’s times. The positive and administrative views of Voiz Koshifi are considered in terms of their relevance to the requirements of the times in ensuring the effectiveness of practical management activities in the administrative management system in modern society.